COLLABORATIVE GOVERNANCE DALAM PERLINDUNGAN ANAK KOTA PEKANBARU TAHUN 2017-2019 - Inggrid Putri Pratiwi; Rury " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research is motivated by Law number 35 of 2014 amendments to Law number 23 of 2002 on Child Protection whose contents become guidelines in the implementation of child protection in the Unitary State of the Republic of Indonesia. Pekanbaru City Government strives to provide protection to children through various agencies that have been created to be responsible for providing welfare for children. Meanwhile, there are many cases that occur concerning violations of children's rights to grow and thrive with protection. The formulation of the problem in this study is how collaborative governance in child protection in pekanbaru city in 2017-2019 and what are the inhibitory factors in its implementation.This study aims to explain collaborative governance in child protection in Pekanbaru City in 2017-2019 and to determine the factors inhibiting the implementation of child protection in Pekanbaru City. The method used in this study is descriptive research with qualitative approach. Research data types are primary and secondary data. The data collection techniques in this study are documentation and interviews. The data analysis technique used is qualitative data analysis.The results showed that collaborative governance in child protection pekanbaru city in 2017-2019 is well established in accordance with the standard operational procedures (SOP) in force. Under the authority of the Mayor as the highest stakeholder in pekanbaru city, there are child protection agencies such as the Office of Women Empowerment and Child Protection (DPPPA), The Health Office and the Police. DPPPA includes Integrated Service Unit for Women and Children Empowerment (UPT P2A) and Community-Based Integrated Child Protection (PATBM). The three institutions collaborate and complement each other in handling cases that occur in children. However, in its implementation there are still shortcomings such as inadequate human resources and insufficient budgets to improve the performance of each institution. Therefore, these factors ultimately hinder the running of excellent collaborative governance in realizing child protection in Pekanbaru City in 2017-2019.Keywords: Collaborative governance, collaboration, child protection.